Players, Mao II e Falling Man: O terror em três versões (publicado em 2014) - Fernandes, Giséle Manganelli [UNESP]; Mariano, Márcia Corrêa de Oliveira [UNESP] (My University, 2013)
This paper aims at analyzing the different approaches to terror in the novels Players (1977), Mao II (1991) and Falling Man (2007), by the American writer Don DeLillo. In Players, terror is shown as something attractive and exciting to a character who leads a very tedious personal and professional life; in Mao II, it is connected to the kidnapping of a poet and the text brings up relevant debates focusing on the contrast related to the power of novelists and terrorists in society; and in Falling Man, the author reviews the tragedy of September 11, in an attempt to try to understand the reasons why the attacks happened. The novels show terrorist actions connected to historical processes and also to the present form of capitalism and globalization. Theoretical texts by Bauman (1998), Eagleton (2005), Freitas (1989), Fraser (2000) will be used to discuss the issues addressed in this paper.

Este trabalho objetiva analisar diferentes tratamentos dados ao terror nos romances Players (1977), Mao II (1991) e Falling Man (2007), do autor americano Don DeLillo. Em Players, o terror mostra-se como algo atrativo e excitante para uma personagem que tem uma vida pessoal e profissional marcada pelo tédio; em Mao II, o terror está conectado ao sequestro de um poeta e o texto traz à baila debates focalizando o contraste entre o poder dos romancistas e o dos terroristas na sociedade; e, em Falling Man, o autor revisa a tragédia do 11 de setembro, em uma tentativa de entender as razões pelas quais os ataques aconteceram. Os romances mostram ações terroristas ligadas a processos históricos e também ao atual status do capitalismo e da globalização. Textos de Bauman (2008), Eagleton (2005), Freitas (1989), Fraser (2000) serão tomados como embasamento teórico para as discussões apresentadas neste trabalho.
Keywords: Don DeLillo; Terrorismo; Capitalismo; Literatura e história; Don DeLillo; Terrorism; Capitalism; Literature and history